2020
DOI: 10.1111/ijd.15302
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyurea: a reappraisal of its cutaneous side effects and their management

Abstract: Hydroxyurea (HU) is known to cause a broad spectrum of cutaneous side effects, ranging from relatively benign to severe. Although dermatologists are often consulted for the treatment of these side effects, a comprehensive resource discussing the different types and their management is lacking. In this study, we conducted a literature search in order to critically evaluate the reported types and management of hydroxyurea's cutaneous side effects, as well as review its mechanism of action, dermatologic uses, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
(157 reference statements)
0
18
0
6
Order By: Relevance
“…Eight out of 10 studies reported an association between HU and NMSC [ 7 , 11 , 15 - 18 , 20 , 22 ]. Two studies found no statistical significance between HU and the development of secondary solid cancers (including cutaneous malignancies) [ 19 , 21 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight out of 10 studies reported an association between HU and NMSC [ 7 , 11 , 15 - 18 , 20 , 22 ]. Two studies found no statistical significance between HU and the development of secondary solid cancers (including cutaneous malignancies) [ 19 , 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…This is consistent with the extremely low incidence of skin cancers in sickle cell patients on relatively low doses of HU for a shorter duration [ 24 ]. Most lesions improved or remained stable after the drug withdrawal [ 7 , 20 ]. In very few cases, tumor recurrence was seen several years after discontinuation of HU [ 16 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations